The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/pharmaceutics13101574
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Aerosol Drug Delivery Options during Adult Mechanical Ventilation in the COVID-19 Era

Abstract: Drug delivery devices used for aerosol therapy during mechanical ventilation to ease the symptoms of respiratory diseases provide beneficial treatment but can also pose challenges. Reflecting the significant changes in global guidance around aerosol usage and lung-protective ventilation strategies, seen in response to the COVID-19 pandemic, for the first time, we describe the drug delivery performance of commonly used devices under these conditions. Here, vibrating mesh nebuliser (VMN), jet nebuliser (JN) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…The dose was then quantified using UV spectrophotometry (WPA Lightwave II; Biochrom Ltd.) at 276 nm and interpolation on a standard curve of serial salbutamol dilutions within a range of 3.125−100 mg/ml, and a recorded R 2 of 0.9998. The drug recovery from the filters using this method was previously reported by our group to be 100 ± 5% 17 …”
Section: Methodsmentioning
confidence: 81%
See 2 more Smart Citations
“…The dose was then quantified using UV spectrophotometry (WPA Lightwave II; Biochrom Ltd.) at 276 nm and interpolation on a standard curve of serial salbutamol dilutions within a range of 3.125−100 mg/ml, and a recorded R 2 of 0.9998. The drug recovery from the filters using this method was previously reported by our group to be 100 ± 5% 17 …”
Section: Methodsmentioning
confidence: 81%
“…Nebuliser placement position is generally directed by clinical protocol or personal preference with international practice surveys suggesting little consistency in approach 28,29 . VMN itself has consistently been shown to deliver the most aerosol in models of mechanical ventilation, across adult and pediatric settings 17,30 . The dry/ventilator side is generally chosen as it is away from the patient and unlikely to be knocked over.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are three prevalent aerosol generator technologies in commercial use, with many new technologies under development or as of yet not commercially available: (I) pressurized metered-dose inhalers (pMDIs); (II) dry powder inhalers; and (III) medical nebulizers [ 110 ]. The choice of device should consider the required target lung dose and the likely patient intervention at the time of administration, as both have been shown to have significant influence [ 111 , 112 ]. The pMDIs are the most prescribed device for lung diseases such as COPD and asthma, but regarding clinical research, nebulizers are the most used instrument [ 113 ].…”
Section: Pulmonary Delivery Of Stem Cell-derived Exosomesmentioning
confidence: 99%
“…Contributing factors for reported variations in aerosol dose delivery include but are not limited to device type [1,6,[10][11][12][13][14], supplemental gas flow rates [11,[15][16][17], equipment [16], breath profiles [6,8,14], and patient interface [13,[18][19][20][21][22]. The aim of this study was to assess the impact of adult and paediatric head model choice on reported aerosol drug delivery.…”
Section: Introductionmentioning
confidence: 99%